1986
DOI: 10.1159/000469274
|View full text |Cite
|
Sign up to set email alerts
|

New Ideas about Enzyme Reactions

Abstract: Since a proper substrate of an enzyme fits its active site closely, adsorption in the active site can occur only if all water is excluded from between them. Any subsequent reaction therefore takes place in the absence of solvent, i.e. as it would in the gas phase. The specificity and high rates of enzyme reactions can be explained immediately in terms of this analogy. Past experimental studies of enzyme mechanisms, based on analogy with reactions in solution, need to be reevaluated. Interpretation of enzyme re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 16 publications
(29 reference statements)
2
24
0
Order By: Relevance
“…According to the desolvation hypothesis (10)(11)(12), an enzyme catalyzes its reaction by creating an environment around the reactants that is similar to the gas phase. This hypothesis stems from the fact that gas-phase calculations (10)(11)(12)(18)(19)(20)(21) as well as analysis of experimental data (15) indicate that the nucleophilic attack in the gas phase (starting from a state with the negative R-O-ion present while Aand BH' are kept at infinite distance) involves a small activation barrier (or no barrier at all), whereas the solution reaction is associated with a significant barrier (15).…”
Section: And 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the desolvation hypothesis (10)(11)(12), an enzyme catalyzes its reaction by creating an environment around the reactants that is similar to the gas phase. This hypothesis stems from the fact that gas-phase calculations (10)(11)(12)(18)(19)(20)(21) as well as analysis of experimental data (15) indicate that the nucleophilic attack in the gas phase (starting from a state with the negative R-O-ion present while Aand BH' are kept at infinite distance) involves a small activation barrier (or no barrier at all), whereas the solution reaction is associated with a significant barrier (15).…”
Section: And 2)mentioning
confidence: 99%
“…A considerable amount of attention has recently been drawn to the proposal that enzymes catalyze reactions by removing water molecules from the reactants, thereby creating an environment similar to the gas phase for the reacting subtrates (the desolvation hypothesis) (refs. [8][9][10][11][12]; see also refs. 20, 29, and 30 for a related discussion).…”
mentioning
confidence: 99%
“…Beyond simple localization, these binding interactions can correctly position the reactive portion of a substrate relative to active site functional groups and relative to other substrates (7,(20)(21)(22)(23)(24)(25). Concomitant with substrate binding solvent is displaced and excluded from the active site and solvent exclusion may be important in shaping the electrostatic environment within the active site (26,27). Indeed, solvent exclusion by substrate binding has been suggested to be important for catalysis in numerous enzymes (e.g., refs.…”
mentioning
confidence: 99%
“…They reported a water activity of 0.004 in their reaction medium, similar to that observed in this study. Other studies have also reported enhancement in enzyme activity by addition of molecular sieves (Dewar, 1986, Dewar et al, 1988Oosterom et al, 1996;Wu and Akoh, 1996). Water also contributes to the hydrolysis of the esters, both substrate (VA) and product (MGA), leading to a net decrease in reaction eciency.…”
Section: Effect Of Watermentioning
confidence: 95%